Transatrial balloon atrial septostomy to facilitate weaning off venoarterial ECMO after pulmonary endarterectomy. Issue 10 (October 2022) - Ak, Koray; Arslanhan, Gökhan; Tire, Yakup; Tosun, Sinan; Kararmaz, Alper; Hanta, İsmail and Yıldızeli, Bedrettin
Atrial septostomy has been the last resort in the management of patients with the right ventricular failure related to pulmonary hypertension before lung transplantation. In this paper, we present a simple and safe technique (transatrial approach) for balloon atrial septostomy in a patient who required central venoarterial extracorporeal membrane oxygenation after pulmonary endarterectomy.